Philosophy of Mathematical Practice — Motivations, Themes and Prospects. Issue 1 (12th February 2019) - Carter, Jessica
ABSTRACT: A number of examples of studies from the field 'The Philosophy of Mathematical Practice' (PMP) are given. To characterise this new field, three different strands are identified: an agent-based, a historical, and an epistemological PMP. These differ in how they understand 'practice' and which assumptions lie at the core of their investigations. In the last part a general framework, capturing some overall structure of the field, is proposed.